2022
DOI: 10.2106/jbjs.cc.22.00503
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Healing of a Posteriorly Displaced Lateral Meniscus Bucket-Handle Tear in a Multiligament Knee Injury

Abstract: Case:Bucket-handle meniscus tears (BHMTs) typically involve the medial meniscus and often occur with concomitant rupture of the anterior cruciate ligament. We report an unusual case of a polytrauma patient who sustained a bicruciate multiligament knee injury (MLKI) with a posteriorly displaced lateral BHMT that spontaneously healed after reduction of the fragment. At the 2-year follow-up, the lateral meniscus was clinically stable without pain.Conclusion:A lateral BHMT with a posteriorly displaced fragment pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, the use of PRP in more unstable meniscal injuries such as radial lesions should not be discarded as it could be a valid option prior to meniscectomy. Previous studies have shown how this type of injury can be repaired instead of removing the meniscus [10, 16, 20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of PRP in more unstable meniscal injuries such as radial lesions should not be discarded as it could be a valid option prior to meniscectomy. Previous studies have shown how this type of injury can be repaired instead of removing the meniscus [10, 16, 20].…”
Section: Discussionmentioning
confidence: 99%